Aesthetic and Educational Functions of 2D Painting on Three-Dimensional Media in Early Childhood Education at PAUD Sabila - Gigih Nuzuli Rahmah; Betty Yulia Wulansari; Nurtina Irsad Rusdiani (Vifada Journal of Education, 2026)
Twenty-first-century learning requires teachers to effectively integrate digital technology into the instructional process. Game-Based Learning (GBL) has emerged as a promising pedagogical approach for creating interactive, collaborative, and learner-centered learning experiences. However, studies that specifically map teachers’ competencies in implementing GBL remain limited. This study aims to: (1) identify the teacher competencies required for GBL implementation; and (2) analyze the challenges and barriers faced by teachers in implementing GBL. This study employed a Systematic Literature Review (SLR) method guided by the PRISMA 2020 protocol, using two international databases, namely Scopus and ERIC. After the identification, screening, and selection stages based on predetermined inclusion and exclusion criteria, 18 relevant articles were obtained as the main sources of analysis. The thematic synthesis results indicate that teacher competencies in GBL implementation are multidimensional, encompassing four interrelated dimensions: digital pedagogical competence, technological literacy and competence, collaborative and social competence, and creativity and innovation. The Technological Pedagogical and Content Knowledge (TPACK) framework was found to be relevant as an integrative mapping tool that connects technological, pedagogical, and content dimensions in game-based learning implementation. The main challenges identified include low levels of teachers’ digital literacy, limited technological infrastructure, and the lack of continuous professional development programs. These findings contribute to the development of teacher training policies and the design of teacher education curricula that are responsive to the demands of the digital era